The UNESCO OER Recommendation: Some Observations from the ICDE OER Advocacy Committee - Ossiannilsson, Ebba; Leonor Ulloa Cazarez, Rosa; Martins Gomes de Gusmão, Cristine; Zhang, Xiangyang; Blomgren, Constance; Chaplin-Cheyne, Trish; Burgos, Daniel (International Review of Research in Open and Distributed Learning, 2023)
In this article, ambassadors of the International Council for Open and Distance Education (ICDE) Open Educational Resources (OER) Advocacy Committee (OERAC) provide a snapshot of regional and global Open Educational Resources (OER) initiatives. This committee has been active since 2017 with membership renewed biannually. The ambassadors work to further OER awareness and understanding, to increase global recognition of OER, and provide policy support for the acceptance and application of OER. This overview highlights national and regional initiatives associated with the UNESCO OER recommendation and the five action areas that include: building capacity and leveraging OER; developing supporting policies; ensuring equity and effectiveness; encouraging sustainable OER model development; and, promoting and facilitating international collaboration. In addition, monitoring and evaluation of the action areas are suggested to be prioritized. This overview is not exhaustive, and much work remains to implement the OER Recommendation at scale, maximize its implementation, connect these recommendations to the United Nation’s Sustainable Development Goals (SDGs), along with the futures of education with a new social contract for education, individuals, and the planet.